2000 Southwest Symposium on Mixed-Signal Design (Cat. No.00EX390)
DOI: 10.1109/ssmsd.2000.836472
|View full text |Cite
|
Sign up to set email alerts
|

A novel fully integrated fan controller for advanced computer systems

Abstract: A low-cost, high-efficiency, compact archilecture of a PWM (pulse-width-modulationr drive fan controller is designed for use in an embedded multicomputer system with an integrated hierarchicai thermal management schema. This pure digital design yields lower cost and higher efficiency than conventional linear drive fan controllers while providing the functionality and advantages of PWM drive fan controllers. The implementation and system integration of this circuit is also described in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, its elegant,¯exible design enables it to implement more complex thermal management algorithms as well. The proposed architecture combined with the fully integrated fan controller [11] used in this system, make it possible to integrate the whole thermal management system inside the CPU with minimum external components and minimum physical size. …”
Section: Resultsmentioning
confidence: 99%
“…However, its elegant,¯exible design enables it to implement more complex thermal management algorithms as well. The proposed architecture combined with the fully integrated fan controller [11] used in this system, make it possible to integrate the whole thermal management system inside the CPU with minimum external components and minimum physical size. …”
Section: Resultsmentioning
confidence: 99%
“…To consider the effect of CPU in heating up the airflow, we measured air temperature at the DIMMs. For the fan control algorithm we assumed a closed loop controller similar to one used in modern systems [5].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a few fan control algorithms have been suggested that operate based on closed loop control schemes to optimize the fan controller [17], [18]. The research in [17] suggests an optimal fan speed mechanism for the blade servers.…”
Section: Related Workmentioning
confidence: 99%
“…if CPU dest has idle core AND no core level migrations in CPU dest then [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]: Intuitively, since the fan power increases exponentially with cooling capacity it is important to balance the heat generation between the sockets in order to lower their fan speed and obtain cooling savings. Spreading is effective as long as there is sufficient imbalance in power consumption between CPU sockets such that the additional spreading migrations can lead to a better balance in socket power and fan speed.…”
mentioning
confidence: 99%